A comparison of fluoroscopic exposure and operative time during treatment of displaced supracondylar elbow fractures in children. (January 2019) - Hand, Cameron; Bresnahan, James J; Hennrikus, William L
Background: Intraoperative fluoroscopy can potentially expose the surgeon to levels of radiation beyond the recommended limits. This study aimed to assess the intraoperative differences between the fixation of types 2 and 3 supracondylar fractures for fluoroscopy time, operative time, direction of displacement, and potential cumulative risk of radiation to the surgeon. Methods: Retrospective chart analysis was used to review 74 consecutive subjects with type 2 or 3 extension supracondylar fractures over a six-year period. Closed reduction and percutaneous pinning with fluoroscopy was used in all cases. Fluoroscopy time and operative time were analyzed based on the fracture type, direction of initial displacement, and the number of K-wires used. Results: Type 2 supracondylar fractures require less fluoroscopy (mean: 16.8 s) and are shorter operations (mean: 19.2 min) when compared to type 3 (26.2 s and 25.1 min; p<0.05). The direction of displacement (posteromedial vs. posterolateral) did not influence operative (23.8 vs. 26.5 min) or fluoroscopy times (27.6 vs. 24.9 s; p>0.05). Conclusions: Type 3 supracondylar fractures utilize more fluoroscopy time and operative time than type 2 fractures. The direction of displacement did not affect fluoroscopy time or operative time. Surgeons who perform large numbers of closed reduction and percutaneous pinning may be exposed to excess amounts of radiation.